4(x+6)-2=0

Simple and best practice solution for 4(x+6)-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+6)-2=0 equation:


Simplifying
4(x + 6) + -2 = 0

Reorder the terms:
4(6 + x) + -2 = 0
(6 * 4 + x * 4) + -2 = 0
(24 + 4x) + -2 = 0

Reorder the terms:
24 + -2 + 4x = 0

Combine like terms: 24 + -2 = 22
22 + 4x = 0

Solving
22 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-22' to each side of the equation.
22 + -22 + 4x = 0 + -22

Combine like terms: 22 + -22 = 0
0 + 4x = 0 + -22
4x = 0 + -22

Combine like terms: 0 + -22 = -22
4x = -22

Divide each side by '4'.
x = -5.5

Simplifying
x = -5.5

See similar equations:

| 〖1/2)〗^(x^2-6)˂(〖1/2)〗^5x | | 15=22=t/3 | | 6x+72=30 | | b^2+36-4=0 | | 3xy-4y^2+18=0 | | 2x^2+14x+20=p(x) | | x^4+34x^2=72 | | 12x-11=8x+37 | | 3x^2+6y^2-12x-48y+90=0 | | 2x^2-1/x=1 | | (3x+5)(x^2+3x-10)=0 | | 50=x*75+2x | | 2x-9/4x-3 | | 10(6x+4)=16(18-4x) | | (0.8)(0.8)-0.4=-0.24 | | 6x^2+25x-119=0 | | (0,2),m=-2/7 | | 4x+13=8x-23 | | (((9x^4/5)(y^1/2))/((121x^4/5)(y^2)))^1/2 | | -7y+x-1=5x+15 | | -x+2(-2x+11)=7 | | b^2+6b=-8 | | (2w+9)(2w-9)= | | 18x-1=107-6x | | 5r+7=13+2r+3r | | 10(4+x)=14x-4 | | 18,069,333.33333=(1/3)440*440*h | | logx(729)=47 | | (7z-3)(5z+2)= | | v^2=-14v | | 6a+19=2(3a+5)+9 | | 11+log(10x+21)=0 |

Equations solver categories